Video-assisted thoracoscopic surgery for ectopic mediastinal parathyroid tumor: subxiphoid and lateral thoracic approach - Nagano, Hiromitsu; Suda, Takashi; Ishizawa, Hisato; Negi, Takahiro; Kawai, Hiroshi; Kawakami, Toru; Tochii, Daisuke; Tochii, Sachiko; Hoshikawa, Yasushi (Journal of Thoracic Disease, 2019)
Background: This study aimed to investigate the initial results of an endoscopic surgical approach for the treatment of intramediastinal ectopic parathyroid adenoma and to evaluate the effectiveness of a single-incision resection using the subxiphoid approach. Methods: Five cases of patients (1.89%) were diagnosed with ectopic mediastinal parathyroid tumor and underwent resection from 2008 to 2017 in Fujita Health University Hospital. They were retrospectively analyzed. Results: Four patients underwent single-port mediastinal tumor resection using the subxiphoid approach and 1 patient underwent multi-port mediastinal tumor resection using the lateral thoracic approach. The operation time was 134±83.52 min, and the amount of blood loss was 81.8±173.41 mL. The rate of conversion to thoracotomy was 0%, and no intraoperative or postoperative complications were observed. The amount of postoperative oral analgesics was 112.83±209.12 tablets, and their administration period was 561.6±1,229.5 days. The length of hospital stay was 4±2.35 days, and the duration of chest tube drainage was 1.33±1.95 days. The patient who underwent multi-port mediastinal tumor resection using the lateral thoracic approach reported postoperative pain. Serum calcium levels decreased from 10.56±1.52 mg/dL preoperatively to 8.96±0.5 mg/dL postoperatively, and serum phosphorous levels increased from 2.84±0.42 mg/dL preoperatively to 3.6±0.51 mg/dL postoperatively. Intact-PTH hormone levels decreased from 221±169.84 pg/dL preoperatively to 70.2±44.28 pg/dL postoperatively. No recurrence of hyperparathyroidism has been observed in any patient. Conclusions: The single-incision mediastinal tumor resection via the subxiphoid approach, without going through the intercostal space, is considered as a useful endoscopic surgical approach for the treatment of mediastinal ectopic parathyroid adenomas due to the limited occurrence of post-thoracotomy pain syndrome and the superior esthetic outcomes associated with the procedure as compared to thoracotomy and median sternotomy.